Peningkatan Prestasi Mata Pelajaran Ekonomi MelaluiPenerapan Model Pembelajaran Problem Based Learning(Pbl) Siswa Kelas X SMA Negeri 2 SukoharjoTahun Ajaran 2015/2016 - Lestari, Sri, Drs. Budi Sutrisno, M.Pd (2016)
The research was purposed to find out whether problem based learning (pbl) program can influence to increasing student's learning achievement or not. One of this kind research was by classroom activities (PTK) which carry out in two cycles. The sample of this research was teachers and 35 student of class X IPS 2 SMA N 2 SUKOHARJO. Data collection method used were interviews, observation, test, range of activity, and documentation. Mean while to analyze, it used data reduction, data presentation, and conclusion. The results showed that learning achievement of economic was increased. It can be seen from indicators as follows. On pre cycle is 16 students (45,71%) were passed while, 19 students (54,29%) failed. On cycle I, 26 students (74,29%) were passed, 9 students (25,71%) failed. On cycle II, 33 students (94,29%) were pass and the rest only 2 students (5,71%) failed. Beside that, school grade also increase which were on pre 65,28 become 74,51, on cycle I and then 82,22 on cycle II. So the conclusion of the research was problem based learning (pbl) program can be said that to increase student's learning achievement of economic students of class X IPS 2 SMA N 2 SUKOHARJO.